2020
DOI: 10.1002/lary.29132
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ACE2 and TMPRSS2 Proteins in the Upper and Lower Aerodigestive Tracts of Rats: Implications on COVID 19 Infections

Abstract: Objective Patients with coronavirus disease 2019 (COVID‐19), caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), exhibit not only respiratory symptoms but also symptoms of chemo‐sensitive disorders. Cellular entry of SARS‐CoV‐2 depends on the binding of its spike protein to a cellular receptor named angiotensin‐converting enzyme 2 (ACE2), and the subsequent spike protein‐priming by host cell proteases, including transmembrane protease serine 2 (TMPRSS2). Thus, high expression of ACE2 and TM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 20 publications
1
34
1
4
Order By: Relevance
“…They also confirmed that ACE2 is expressed in human oral tissues, especially enriched in dorsal tongue more than gingival and buccal tissues. Sato et al [ 149 ] found that ACE2 and TMPRSS2 responsible for the viral cellular entry are co-expressed in the taste buds of tongue foliate papillae of rats. Wang et al [ 150 ] revealed that ACE2 is enriched in a subpopulation of mouse tongue epithelial cells.…”
Section: Possible Mechanisms Of Gustatory Dysfunctionmentioning
confidence: 99%
“…They also confirmed that ACE2 is expressed in human oral tissues, especially enriched in dorsal tongue more than gingival and buccal tissues. Sato et al [ 149 ] found that ACE2 and TMPRSS2 responsible for the viral cellular entry are co-expressed in the taste buds of tongue foliate papillae of rats. Wang et al [ 150 ] revealed that ACE2 is enriched in a subpopulation of mouse tongue epithelial cells.…”
Section: Possible Mechanisms Of Gustatory Dysfunctionmentioning
confidence: 99%
“…Most patients with these disorders recover in 14 days, but some patients remain symptomatic for longer periods [52]. ACE2 may be expressed in the taste buds [53], and these long-lasting disorders may be directly affected by the virus.…”
Section: Sequelae Of Covid-19mentioning
confidence: 99%
“…Viral entry needs viral protease activity, mainly transmembrane protease serine 2 (TMPRSS2) or eventually cathepsin B/L. ACE2 is present on the surface of endothelial cells, and many other cells in the lower (lung) and upper respiratory tract (nasal epithelium), heart, brain, intestines, liver, kidneys, testicles, cornea and salivary glands [3]. Infection ranges from asymptomatic to mild (about 50% of infected subjects), moderate, or severe.…”
Section: Introductionmentioning
confidence: 99%
“…The most common symptoms of COVID-19 are fever, Copyright © Yordan Benhamou GMR.000615. 5 (3).2021 chills, dry cough, dyspnea, diarrhea, headache, unusual fatigue, alteration of the general state. Sudden loss of smell (anosmia) or taste (ageusia) occurs in approximately 60% of mild to moderated forms of COVID-19, and regresses within a few weeks [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation